2009
DOI: 10.1177/1524839907306406
|View full text |Cite
|
Sign up to set email alerts
|

Implementation, Outcomes, and Lessons Learned From a Collaborative Primary Health Care Program to Improve Diabetes Care Among Urban Latino Populations

Abstract: A collaborative primary health care service demonstration program was conducted to improve diabetes care among limited English-proficient (LEP) Latino patients. The intervention provided a multilevel approach aimed at patients and health care providers: Community health workers (CHWs) were mobilized to offer diabetes education in Spanish to LEP Latino diabetes patients, and health professions students and providers were offered intensive Spanish language training and cultural competency workshops. Positive out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…Community activities included community engagement and participation Alexy and Elnitsky, 1996;Billingham and Perkins, 1997; Table 2 Articles included in scoping review listed by first author Alexy and Elnitsky (1996) Elster et al, 2002;Harrison et al, 2006;PHRED, 2006;Wedel et al, 2007;McElmurry et al, 2009), improving quality of care (Ferguson et al, 1992;Alexy and Elnitsky, 1996;Lundeen et al, 1997;Harris et al, 2003;Heller and Goldwater, 2004), containing costs Voelker, 1994; The Committee on Medicine and Public Health, 1997; Welton et al, 1997;Hripcsak et al, 1999;Williams et al, 1999), enhancing evidence-informed practice Jordan et al, 1998;Hopayian et al, 2005;Larson et al, 2006) and improving emergency planning and response (Hogg et al, 2006b;Harris et al, 2007;Mack et al, 2007;Pierce et al, 2007;Taylor et al, 2007). Collaboration was, however, also negatively impacted by the rapid and constant change created by healthcare reform Hopayian et al, 2005).…”
Section: Activities Carried Out In Collaborationsmentioning
confidence: 99%
“…Community activities included community engagement and participation Alexy and Elnitsky, 1996;Billingham and Perkins, 1997; Table 2 Articles included in scoping review listed by first author Alexy and Elnitsky (1996) Elster et al, 2002;Harrison et al, 2006;PHRED, 2006;Wedel et al, 2007;McElmurry et al, 2009), improving quality of care (Ferguson et al, 1992;Alexy and Elnitsky, 1996;Lundeen et al, 1997;Harris et al, 2003;Heller and Goldwater, 2004), containing costs Voelker, 1994; The Committee on Medicine and Public Health, 1997; Welton et al, 1997;Hripcsak et al, 1999;Williams et al, 1999), enhancing evidence-informed practice Jordan et al, 1998;Hopayian et al, 2005;Larson et al, 2006) and improving emergency planning and response (Hogg et al, 2006b;Harris et al, 2007;Mack et al, 2007;Pierce et al, 2007;Taylor et al, 2007). Collaboration was, however, also negatively impacted by the rapid and constant change created by healthcare reform Hopayian et al, 2005).…”
Section: Activities Carried Out In Collaborationsmentioning
confidence: 99%
“…customs, medical practices, folk remedies, etc. ), demographics, and politics is essential for a productive project outcome [34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…16 Patients with chronic disease have reported that they need to better understand their condition in order to appropriately manage it and that CHWs need to be effective communicators and respectful of the patient. 27 The DEP leadership sought to meet these patient needs through focused recruitment of CHWs within the targeted communities and extensive team-based training.…”
Section: Community Health Worker Recruitment and Trainingmentioning
confidence: 99%
“…15 Community health workers can provide time-intensive and community-based diabetes self-training and can serve as a bridge between patients and providers. 11,16 Patients are more likely to trust a peer from a similar background who understands the patient's culture. 16 This level of trust allows patients and CHWs to work together to improve diabetes-specific behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation